Key account management : strategies to leverage information, technology, and relationships to deliver value to large customers - Le Bon, Joel (College teacher) (Selling and sales force management collection., 2015)
Now more than ever, companies are faced with a critical and challenging truth. Today's customer is demanding more attention, superior service, and the expertise of a dedicated sales team. Suppliers must make difficult choices to determine how to allocate limited resources, including which customers receive the highest level of service. Increasingly, supply side organizations are working to design and implement key account programs to meet or exceed these expectations. Key account management is a specific business strategy that involves complex sales processes, large-scale negotiations, and the alignment of multiple internal and external stakeholders. This multi-pronged process is anything but straightforward, and the business world is filled with examples of key account programs that have not achieved the expected results. This book addresses the strategic challenges facing top executives and sales leaders as they build strategies to better manage their key accounts.